Common home: our responsibility, our survival - Michell Ângelo Marques Araújo (Rev Rene)
We have noticed how the reflections raised in the 2016 Ecumenical Fraternity Campaign are appropriate, timely and mobilizing to protect, promote and ensure life, and its theme is – “common home: our responsibility”. Due to the fact that this year has an ecumenical character, the campaign is not limited to the Catholic scope, but includes the Churches that take part in the Brazilian National Council of Christian Churches (as per its Portuguese acronym), thus inviting society to a broader discussion about this issue, with an emphasis on sewage disposal.